Clinical Impact of Solifenacin on Generic and Symptom-Specific Quality of Life for Females with Overactive Bladder: Using the Overactive Bladder Symptom Score and Rand Medical Outcomes Study 36-Item Health Survey - YANO, Masashi; SUZUKI, Hiroyoshi; KAMIYA, Naoto; KATO, Tomonori; NOMURA, Kazushi; KURAMOCHI, Hiroaki; OHTA, Sho; MIKAMI, Kazuo; NAKATSU, Hiroomi; OKANO, Tatsuya; ONISHI, Tetsuro; ICHIKAWA, Tomohiko (Lower urinary tract symptoms, 2013)
Objectives: We evaluated the effectiveness of antimuscarinic treatment on disease‐specific and generic quality of life (QoL) in females with clinically diagnosed overactive bladder (OAB) by prospectively analyzing improvements in the overactive bladder symptom score (OABSS) and the Rand Medical Outcomes Study 36‐Item Short Form Health Survey (SF‐36). Methods: We prospectively recruited newly diagnosed female patients with OAB. Pretreatment disease‐specific symptoms were documented, and generic QoL questionnaires were administered. All subjects received solifenacin 5 mg/day for >8 weeks. Symptoms and general health‐related QoL (HRQoL) were assessed using the OABSS and SF‐36, respectively. Other objective variables, such as maximum urinary flow rate and postvoid residual urine volume, were also evaluated. Results: Seventy‐eight subjects met all inclusion criteria and no exclusion criteria. After 8 weeks, the mean OABSS decreased by approximately 50% compared with baseline (from 9.1 ± 2.8 to 4.5 ± 3.6). All individual scores in OABSS improved after administration of solifenacin. Before treatment, the scores of the study subjects in all SF‐36 domains were significantly worse than the age‐ and gender‐adjusted Japanese national norms (P < 0.01), except the vitality (VT) scale. Intra‐group comparisons between age groups showed worse mental health (MH) scores in all age groups. In the OAB group, three mean SF‐36 scales (physical function [PF], VT, and MH) significantly improved after treatment. Conclusion: Treatment of OAB with solifenacin is associated with significant improvement in generic HRQoL and disease‐specific symptoms at 8 weeks after drug administration. Particularly for generic HRQoL as measured by the SF‐36, solifenacin treatment effectively improves three SF‐36 scores: PF, VT, and MH.